Comparative Characteristics of the Metabolic Syndrome Prevalence in Patients With Schizophrenia in Three Western Siberia Psychiatric Hospitals - Kornetova, Elena G.; Kornetov, Alexander N.; Mednova, Irina A.; Goncharova, Anastasia A.; Gerasimova, Valeria I.; Pozhidaev, Ivan V.; Boiko, Anastasiia S.; Semke, Arkadiy V.; Loonen, Anton J. M.; Bokhan, Nikolay A.; Ivanova, Svetlana A. (Frontiers in Psychiatry, 2021)
Objective: The purpose of this study was to compare the prevalence of MetS and the associated sociodemographic, clinical, and pharmacotherapeutic characteristics of patients with schizophrenia in three psychiatric hospitals in the West Siberian region. Methods: Patients with a clinical diagnosis of schizophrenia (ICD-10: F20) and an age between 18 and 60 years were included in the study after giving informed consent. Metabolic syndrome was diagnosed according to the International Diabetes Federation criteria. This research was carried out at three Western Siberian psychiatric hospitals in Kemerovo, Tomsk, and Omsk. The study population included respectively 94, 131, and 91 inpatients with schizophrenia. We carried out schizophrenia symptoms assessment by PANSS, antipsychotic therapy evaluation, anthropometry, and biochemical analysis. Statistical Analysis included the Shapiro-Wilk test, non-parametric Kruskal-Wallis H test for independent samples, Mann-Whitney U-test for independent samples, the chi-square test, stepwise multiple regression analyses. The level of significance was p-values less than 0.05. Results: The metabolic syndrome prevalence was higher among patients in Tomsk (36.6%), compared with Kemerovo (20.2%, p = 0.008) or Omsk (18.7%, p = 0.004), mainly due to the high prevalence of abdominal obesity, while men from Tomsk were more susceptible to this condition than men from other regions (p < 0.05). Patients from Omsk had the highest severity schizophrenia symptoms according to PANSS, and patients from Tomsk had the lowest severity of positive symptoms according to PANSS. Patients from Tomsk had the minimum duration of antipsychotic therapy compared with the patient from Kemerovo (p = 0.017) and from Omsk (p = 0.000019), but most patients from Tomsk received second-generation atypical antipsychotics, while patients from Omsk received mainly conventional antipsychotics (p = 0.0001). Multiple regression analysis showed that metabolic syndrome associated with schizophrenia duration and body mass index, although the association was not so strong (adjusted R2 = 0.2435, p < 0.0001). Discussion: The study illustrates that in different psychiatric hospitals within the same region, the prevalence of metabolic syndrome in patients with schizophrenia can vary significantly, which dictates the need to look for opportunities to minimize the risk of its occurrence, taking into account the experience of each hospital.